2015
DOI: 10.1186/s12916-015-0346-z
|View full text |Cite
|
Sign up to set email alerts
|

Prescriber and patient-oriented behavioural interventions to improve use of malaria rapid diagnostic tests in Tanzania: facility-based cluster randomised trial

Abstract: BackgroundThe increasing investment in malaria rapid diagnostic tests (RDTs) to differentiate malarial and non-malarial fevers, and an awareness of the need to improve case management of non-malarial fever, indicates an urgent need for high quality evidence on how best to improve prescribers’ practices.MethodsA three-arm stratified cluster-randomised trial was conducted in 36 primary healthcare facilities from September 2010 to March 2012 within two rural districts in northeast Tanzania where malaria transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 37 publications
2
42
1
Order By: Relevance
“…§Tanz1 recorded medicines actually obtained by patients; other studies recorded medicines prescribed. ¶Figure is lower than that reported in primary paper 39 because the present analysis included all patients with data, rather than only patients defined by study as mRDT-eligible. **Only subset of patients (n=497) in Uga-priv followed up after consultation to collect data on medicines prescribed.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…§Tanz1 recorded medicines actually obtained by patients; other studies recorded medicines prescribed. ¶Figure is lower than that reported in primary paper 39 because the present analysis included all patients with data, rather than only patients defined by study as mRDT-eligible. **Only subset of patients (n=497) in Uga-priv followed up after consultation to collect data on medicines prescribed.…”
Section: Resultsmentioning
confidence: 70%
“…Detailed descriptions of the individual studies are available in open access publications. [36][37][38][39][40][41][42][43] We included in the analysis studies that met the following criteria: evaluated an intervention to implement rapid diagnostic tests for malaria in settings where participating providers could prescribe both antimalarials and antibiotics, compared sites with and without the intervention, documented prescriber behaviour as a primary outcome, and collected individual patient data on diagnostic test results and treatments prescribed including antibiotics. Tables 1 and 2 present descriptions of the nine studies meeting these criteria.…”
Section: Overview Of Studies Included In Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…They also demonstrated that enhanced training has no effect on compliance with RDT positive result and adherence to treatment guidelines [23]. Cundill et al in another study conducted in Tanzania also demonstrated that training may influence compliance with RDT negative result, but has no effect on compliance with RDT positive result [24]. Some other related study conducted in Burkina Faso revealed that even enhanced training has no effect on compliance with RDT negative results [25] but rather the availability and access to alternative diagnostic methods for other common febrile illnesses [14].…”
Section: Discussionmentioning
confidence: 98%
“…The eight studies included in this analysis were conducted between 2007 and 2013 in Cameroon, Ghana, Nigeria, Tanzania, and Uganda [20][21][22][23][24][25][26][27]. The studies assessed the introduction of mRDTs among health care providers in public health centres (Cam1, Ghan1, Tanz1, Tanz2, Uga1), public and private facilities (Nige1), private drug shops (Uga3), and community health programmes (Uga2).…”
Section: Studies Included In the Analysismentioning
confidence: 99%